AB0838 Bone Metabolism Biomarkers in Tunisian Hemodialysis Patients. (10th June 2014) - Slouma, M.; Sahli, H.; Smaoui, W.; Mourad, M.; Hadj Salah, A.; El Euch, M.; Abdelmoula, J.; Ben Moussa, F.; Cheour, E.
Abstract : Background: Although bone biopsy is a golden standard in the diagnosis of chronic kidney disease mineral and bone disorders (CKD-MBD), this method is invasive and repetitive evaluation of bone status cannot be possible. Objectives: The aim of this study was to clarify the issue of bone metabolic markers in regular hemodialysis (HD) patients. Methods: A prospective study included 90 patients under HD therapy over a three month period. Hematological and biochemical blood samples were collected after at least 10 h of fasting just prior to the HD session. One bone formation markers: bone-specific alkaline phosphatase (BAP) and one bone resorption marker carboxy-terminal telopeptides of type 1 collagen (CTx) were selected for study. Both statistical and descriptive analyses were performed. Results: Ninety patients were included: 58 male (64%) and 32 female (36%). The mean age was 53.01±14.66. The body mass index was 25.79±4.67 kg/m 2 . The mean age of onset of nephropathy was 48.40±15.09. It was diabetic nephropathy in 30 cases, glomerulonephritis in 34 cases, vascular nephropathy in 6 cases, amyloidosis in 1 case, polycystic in 4 cases, tubulointerstitial nephropathy in 9 cases and indeterminate nephropathy in 6 cases. The mean age of onset of HD therapy was 50.06±14.82 years. The levels of BAP and CTx showed a strongly positive correlation (r=0.56, p<0.001). Moreover, both circulating BAP and CTx levels showed positive correlations with serum intact parathyroid hormone levels (r=0.63, p=0.026 and r=0.58, p=0.003 respectively). Conclusions: The determination of serum intact parathyroid hormone has been used for many years as an indirect predictor of CKD-MBD. The introduction of modern biomarkers of bone metabolism offers the possibility of a direct assessment of bone metabolism. BAP is a bone formation marker, it is not influenced by either renal dysfunction or the HD procedure because it is exclusive metabolized in the liver. Thus, serum BAP concentration can provide useful information about the rate of bone remodeling in HD patients. Even if CTX is cleared by the kidney, our study showed that circulating BAP and CTx levels are strongly correlated with serum PTH levels. Therefore, in HD patients, bone metabolic markers including BAP and CTx may accurately reflect bone turnover. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6000